Los emblemata physico-ethica de Nicolás Taurello - Mañas Núñez, Manuel (2019)
Este artículo estudia la obra Emblemata physico-ethica (1595, 1602 y 1617) de Nicolás Taurello. Se tratan la obra y sus ediciones, las circunstancias de composición y las intenciones y temas del libro.
This paper studies the work Emblemata physico-ethica (1595, 1602 and 1617) by Nicolaus Taurellus. The works and its editions, the circumstances of composition and the intentions and topics of the book are treated.
Keywords: Taurellus, Nicolaus, -- 1547-1606; Lengua latina; Naturaleza; Libros de emblemas; Ética